Filantropi Islam: Praktek dan Kontribusinya terhadap Ketercapaian Sustainable Depvelopment Goals (SDGs) - Nasrulloh, Nasrulloh (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
In the last decade, the rise of Islamic Philanthropic Foundation phenomenon in Indonesia is still has a spotlight in people glance. Islamic Philanthropy Foundation is a practice of generosity in the Islamic tradition through zakat, infaq, and wakf. In this paper, the author tries to map the contribution of Islamic philanthropic institutions to achieve the Sustainable Development Goals (SDGs). The results of this research showed that the Islamic Philanthropy Fondation, in this study specializing in National Zakat Distributor Foundation (Laznas) Yatim Mandiri, had made a positive contribution to the achievement of the SDGs. Several programs have been carried out such as the ZISWAF fundraising for the independence of orphans and the underprivileged through economic empowerment, education, health and welfare in line with the main objectives of the SDGs. The achievements that have been achieved by Islamic Philanthropic Foundation need to be supported by all stakeholder so that the achievement of sustainable development goals in Indonesia becomes a necessity.